Using urea formaldehyde and polyethyleneglycol as seed coating to improve Maize seed qualities - Khunkeaw S. (2017)
The objective of this experiment was to determine the effectiveness of various ratio of nitrogen slow release fertilizer urea formaldehyde and polyethyleneglycol (PEG 6000) concentration for coating maize seeds. The seeds were coated with urea formaldehyde at the concentration 0.2, 0.6, 0.8, 1.0, 1.2 gN in combination with 3% (w/v) of PEG 6000. The qualities of coated seed were assayed by germination percentage, germination index, seedling vigor classification, shoot and root growth rate and accelerated aging test. The results showed that coated seeds with urea formaldehyde at 0.4 gN and 3% (w/v) of PEG 6000 provided promising results in germination percentage, germination index, seedling vigor classification and accelerated aging test comparing to uncoated seeds.